Analysing the Effect of Tourism on Economic Growth: In the Case of Selected Small Island Developing States - Roudi, Samira (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This study used a relatively novel model of heterogeneous panel autoregressive distributed lag cointegration (ARDL) for reanalyzing Granger causality association amongst tourism growth and economic development in the selected small island developing states (SIDSs). Furthermore, energy usage and foreign direct investment (FDI) are incorporated as alternate development factors, from 1995 to 2014. For a complete and robust analysis, a panel of 10 SIDSs was applied in this study like Bahrain, Cyprus, the Dominican Republic, Haiti, Jamaica, Iceland, Malta, Mauritius, Sri Lanka, and Singapore between 1995 and 2014 from the online database of World Bank. Subsequently agreeing on the heterogeneous nation-state impact, significant equilibrium long-run association amongst tourism, energy usage, FDI, and GDP, with a reasonable convergence ratio is verified. Empirical findings of the study support tourism-induced growth, tourism-induced energy consumption, tourism-induced investment, and the energy consumption-economic growth association in the case of SIDSs. Our empirical results resound with the relevant studies and offer the main policy proposition in the case of SIDSs. Keywords: cointegration; dynamic panel model; economic growth; granger causality; small island developing states tourism earnings.

ÖZ: Bu çalışmada, gelişmekte olan küçük ada ülkelerindeki (SIDS) turizm ve ekonomik kalkınma arasındaki Granger nedensellik ilişkisi yeniden analiz edilmiştir. Bunun için nispeten yeni bir heterojen panel otoregressif dağıtılmış gecikmeli eşbütünleşme modeli kullanılmıştır (ARDL). Ayrıca, alternatif kalkınma faktörleri olarak 1995'ten 2014'e kadar olan enerji tüketimi ve doğrudan yabancı yatırım (DYY), oranlarıda çalışmaya dahil edilmiştir.Tam ve sağlam bir analiz yapmak için, gelişmekte olan küçük ada ülkelerinden(SIDS), Bahreyn, Kıbrıs, Dominik Cumhuriyeti, Haiti, Jamaika, İzlanda, Malta, Mauritius, Sri Lanka ve Singapur’un 1995-2014 yıllarına ait verileri kullanılmıştır. Diğer yandan, heterojen ulus devlet etkisi konusunda anlaşmaya varıldığında, ılımlı bir yakınsama oranı ile, turizm, enerji tüketimi, doğrudan yabancı yatırımı(DYY) ve gayri safi yurtiçi hasıla(GSYİH) arasında uzun vadede pozitif ve önemli bir dengede birleşme olduğu doğrulanmaktadır. Çalışmanın ampirik sonuçları, gelişmekte olan küçük ada ülkelerinde (SIDS) turizm kaynaklı büyümeyi, turizm kaynaklı enerji tüketimini, turizm amaçlı yatırımları ve enerji tüketimi ve ekonomik büyüme arasındaki ilişkiyi desteklemektedir. Ampirik sonuçlarımız mevcut bulgularla benzerlik göstermekte olup, gelişmekte olan küçük ada ülkeleri (SIDS) için temel politik sonuçlar sunmaktadır. Anahtar Kelimeler: eşbütünleşme; ekonomik büyüme;; granger nedensellik; dinamik panel modeli; gelişmekte olan küçük ada ülkelerinin turizm gelirleri
Doctor of Philosophy in Tourism Management. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Tourism, 2019. Co-Supervisor: Prof. Dr. Salih Katırcıoğlu and Supervisor: Prof. Dr. Hüseyin Araslı.
Keywords: Tourism; Tourism--Economic Growth--Island Economy; Cointegration; dynamic panel model; economic growth; granger causality; small island developing states tourism earnings